VD_FINDINFO HC / 2011 / 236 vom 13. April 2011 - VD Tribunal cantonal (2011)
APPEL EN CAUSE, DÉCISION INCIDENTE, ACTION EN DIVORCE, DROIT TRANSITOIRE | 83 al. 1 let. a CPC, 83 al. 1 let. c CPC, 84 al. 3 CPC, 404 CPC (CH), 405 al. 1 CPC (CH)